Biofilm Formation in Methicillin-Resistant Staphylococcus aureus Isolated in Cystic Fibrosis Patients Is Strain-Dependent and Differentially Influenced by Antibiotics - Boudet, Agathe; Sorlin, Pauline; Pouget, Cassandra; Chiron, Raphaël; Lavigne, Jean-Philippe; Dunyach-Remy, Catherine; Marchandin, Hélène (Frontiers in Microbiology, 2021)
Cystic fibrosis (CF) is a genetic disease with lung abnormalities making patients particularly predisposed to pulmonary infections. Staphylococcus aureus is the most frequently identified pathogen and multidrug-resistant strains (MRSA, methicillin-resistant S. aureus) have been associated with more severe lung dysfunction leading to eradication recommendations. Diverse bacterial traits and adaptive skills, including biofilm formation, may however make antimicrobial therapy challenging. In this context, we compared the ability of a collection of genotyped MRSA isolates from CF patients to form biofilm with and without antibiotics (ceftaroline, ceftobiprole, linezolid, trimethoprim and rifampicin). Our study used standardized approaches not previously applied to CF MRSA, the BioFilm Ring test® (BRT®), the Antibiofilmogram® and the BioFlux™ 200 system which were adapted for use with the artificial sputum medium mimicking conditions more relevant to the CF lung. We included 63 strains of 10 multilocus sequence types isolated from 35 CF patients, 16 of whom had chronic colonization. The BRT® showed that 27% of the strains isolated in 37% of the patients were strong biofilm producers. The Antibiofilmogram® performed on these strains showed that broad-spectrum cephalosporins had the lowest minimum biofilm inhibitory concentrations (bMIC) on a majority of strains. A focus on 4 chronically-colonized patients with inclusion of successively isolated strains showed that ceftaroline, ceftobiprole and/or linezolid bMICs may remain below the resistance thresholds over time. Finally, studying the dynamics of biofilm formation by strains isolated 3 years apart in one of these patients using BioFlux™ 200 showed that inhibition of biofilm formation was observed for up to 36h of exposure to bMIC and ceftaroline and ceftobiprole had a significantly greater effect than linezolid. This study has brought new insights into the behavior of CF MRSA which has been little studied for its ability to form biofilm. Biofilm formation is a common characteristic of prevalent MRSA clones in CF. Early biofilm formation was strain-dependent, even within a sample, and not only observed during chronic colonization. Ceftaroline and ceftobiprole showed a remarkable activity with a long-lasting inhibitory effect on biofilm formation and a conserved activity on certain strains adapted to the CF lung environment after years of colonization.